HUBUNGAN EDUKASI CUCI TANGAN TERHADAP PENGETAHUAN, SIKAP, KEMAMPUAN KELUARGA DI RUMAH SAKIT X PALEMBANG - Angela Satiti; Sanny Frisca; Vausta Nurjanah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Families of patients who are in the hospital have an important role in preventing nosocomialinfections by increasing the knowledge and attitude of hand washing in hospitals by increasingtheir knowledge and attitude of eating will also increase the ability to wash hands. However, theimplementation of hand washing in the patient's family has not run optimally due to variousreasons. The patient's family said that they did not know how to wash their hands properly andsome said that they did not wash their hands because the patient's disease was not contagious.this study aims to determine the relationship of hand washing education to knowledge, attitudesand abilities of family members in the X Palembang Hospital.Method: This research is aquantitative type of research using quasi experimental with a Non Equavalent Control Group planand a sample of 112 respondents used purposive sampling technique. The data analysis techniqueused is the Fisher Exact.The results of this study indicate that there is a relationship between handwashing education to the knowledge, attitudes, ability, of the families of patients at X PalembangHospital (p value= 0.001<0.005), For this reason, the role of nurses as educators is needed,providing counseling to families of patients treated at Hospital so that nosocomial infections canbe prevented.